Um olhar dialógico sobre a atividade de revisão de textos escritos: entrelaçamento dizeres e fazeres - Oliveira, Risoleide Rosa Freire de (2007)
This research deals with the activity of text revision. It aims at understanding the work of the text reviewer, taking into consideration the professional experiences of the subjects who work in the area. It s theoretical basis comes from Bakhtin Circle, mainly the concept of verbal interaction formulated from reflections on language used in different spheres of human activities, which implies the notions of discourse genres, alterity, as well as exotopy. The methodology follows the tradition of the qualitative and interpretative research. The data is composed of the statements of text reviewers both in handbooks and interviews, as well as of the description of the researcher s own experience as text reviewer. The results indicate that the revision activity needs to be orientated by a dialogical conception of language, which takes into consideration the interaction between the reviewer and the author, aiming the text finalization